A new species of Tricorythodes Ulmer from Colombia and additional notes on T. serratus (Baumgardner & Ávila) (Ephemeroptera: Leptohyphidae) - López, Tatiana Cárdenas; Flowers, Ralph Wills; Dias, Lucimar Gomes (Zootaxa, 2022)
A new species of Tricorythodes is described and illustrated based on nymphs from Colombia. Legs, mouthparts and other parts of the body were photographed through SEM and molecular characterization was performed by amplification of the COImt gene. Tricorythodes carare sp. nov. shows close affinities with T. serratus (Baumgardner & Ávila), both sharing a similar coloration pattern and the presence of chalazae on femora. The new species can be distinguished from T. serratus and all the species of the genus by the following combination of characters: maxillary palp 3-segmented, with apical setae; dorsal surface of median and hind femora with a longitudinal row of 5 to 9 chalazae serrated in the apex, tarsal claws with 4 or 5 marginal denticles and with 1–3 submarginal denticles; posterior margin of the abdominal terga with serrated chalazae in the apex. SEM images and distance analysis of the partial sequences of the COI gene were useful to discriminate the new species from T. serratus (genetic divergence 17–19%). An additional undescribed species of this group is reported from Esmeraldas in Ecuador and for the departments of Sucre and Chocó in Colombia, but it is not described here because of the low number of individuals and the lack of DNA integrity. What is known under the name Tricorythodes serratus is suspected to be a species complex.